Dynamic and Rapid Changes in Viral Quasispecies by Udps in Chronic Hepatitis C Patients Receiving Telaprevir-Based Therapy. Issue 5 (July 2013) - Trimoulet, Pascale; Pinson, Patricia; Papuchon, Jennifer; Foucher, Juliette; Vergniol, Julien; Chermak, Faiza; Wittkop, Linda; Castaing, Nadège; Merrouche, Wassil; Reigadas, Sandrine; Molimard, Mathieu; Kann, Michael; et al.
Background: Telaprevir (TVR) is a protease inhibitor (PI) used in chronic hepatitis C treatment with pegylated interferon plus ribavirin. We analysed the prevalence and kinetic development of TVR resistance upon treatment. Methods: A total of 24 cirrhotic patients (genotype 1a, n =8; genotype 1b, n =16) previously non-responders to standard therapy were treated with TVR-based therapy. The distribution of TVR-resistant variants was assessed at every HCV-RNA-positive time point by 454 ultra-deep pyrosequencing (UDPS) during a mean follow-up period of 9.4 months. Results: A median of 6, 837 reads/specimen was studied. Based on control UDPS, we considered mutations as real when present >0.4%. TVR-resistant variants were found at baseline in 8/24 patients (33.3%). Four of the 24 patients (16.7%), all genotype 1a, did not achieve HCV RNA<100 IU/ml between week (W)2 and W12 and stopped treatment. No statistical significant difference was observed in the prevalence of resistant mutants between responders and non-responders (25% [5/20] and 75% [3/4], respectively). The proportion of genotype 1a patients with R155K/T/Q at baseline was higher in non-responders than in responders (50% versus 0%). During treatment failure, significant enrichment in V36A/M and R155K/T/Q was observed but their frequency reverted back to baseline after TVR discontinuation. Conclusions: TVR-resistant variants are widely present at baseline. The presence of TVR-resistant mutants at baseline, even in high abundance (>20%), did not always preclude TVR treatment success. The detection of R155K/T/Q at baseline may predict failure in genotype 1a patients. At failure, which occurred in genotype 1a patients, a significant enrichment in V36A/M and R155K/T/Q was observed.